PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN - Ulum, Muhammad Fariz Bahrul (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this research is to determine the influence of Celebrity Endorser and Brand Image on purchasing decisions. The research method used is a survey method with a quantitative research design. The data collection process uses an instrument in the form of a questionnaire distributed via social media platforms. The data analysis technique used is multiple linear regression analysis which was tested using SPSS software The research results show that: (1) Celebrity Endorser influences purchasing decisions, and (2) Brand Image influences purchasing decisions